Mapping monophonic midi tracks to vibrotactile stimuli using tactile illusions. - Remache-Vinueza, Byron; Trujillo-León, Andrés; Clim, Maria-Alena; Sarmiento-Ortiz, Fabián; Topon-Visarrea, Liliana; Refsum Jensenius, Alexander; Vidal-Verdú, Fernando (Springer, 2022)
In this project, we propose an algorithm to convert musical features and structures extracted from monophonic MIDI files to tactile illusions. Mapping music to vibrotactile stimuli is a challenging process since the perceptible frequency range of the skin is lower than that of the auditory system, which may cause the loss of some musical features. Moreover, current proposed models do not warrant the correspondence between the emotional response to music and the vibrotactile version of it. We propose to use tactile illusions as an additional resource to convey more meaningful vibrotactile stimuli. Tactile illusions enable us to add dynamics to vibrotactile stimuli in the form of movement, changes of direction, and localization. The suggested algorithm converts monophonic MIDI files into arrangements of two tactile illusions: ``phantom motion'' and ``funneling''. The validation of the rendered material consisted of presenting the audio rendered from MIDI files to participants and then adding the vibrotactile component to it. The arrangement of tactile illusions was also evaluated alone. Results suggest that the arrangement of tactile illusions evokes more positive emotions than negative ones. This arrangement was also perceived as more agreeable and stimulating than the original audio. Although musical features such as rhythm, tempo, and melody were mostly recognized in the arrangement of tactile illusions, it provoked a different emotional response from that of the original audio.
https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Tacto; Psicología fisiológica; Biosensores; Audio tactile rendering; MIDI; Monophonic music; Tactile illusion; Vibrotactile stimuli